Dual-Band Aperture-Coupled Rectenna For Radio Frequency Energy Harvesting - Mohd Noor, Faza Syahirah; Zakaria, Zahriladha; Lago, Herwansyah; Meor Said, Maizatul Alice (John Wiley & Sons Inc., 2019)
The article presents a dual‐band aperture‐coupled rectenna for radio frequency (RF) energy harvesting at 2.45 and 5 GHz application. The rectenna consists of a dual‐band π‐shaped slot‐etched aperture‐coupled antenna, designed at the lower substrate of two FR4 substrate layers and a dual‐band rectifier. The proposed antenna design also introduces the harmonic suppression of third‐ and higher order harmonics, ranging from 6 up to 10 GHz from the asymmetrical stubs design at the transmission feedline. The dual‐band rectifier is designed to operate at 2.45 and 5 GHz frequency, successfully achieving high conversion efficiency at 68.83% and 49.90% with the optimum load resistor of value 700 Ω and 1.1 kΩ. The minimum DC voltage of 0.167 and 0.236 V with 0 dBm RF input power can be increased when greater RF power is being applied to it, increasing its flexibility to cater various low‐power applications.